DISPOSAL OF IRON-CONTAINING WASH WATER - Anastasia Vladimirovna Moskvicheva; Anastasia Andreevna Sakharova; Aleksey Konstantinovich Cherkesov; Zulfira Kaitarbekovna Ibragimova (Современная наука и инновации)
The main results of investigation of the process of sedimentation of suspension based on the study of factors affecting the efficiency of the wash water clarification of water supply stations. The obtained optimal length horizontal sedimentation tank for rinsing water treatment rapid filters.